Civility Practices in Workplace and Marketing Outcomes in Financial Institutions: A Case of I&M Bank Rwanda Ltd - Rosette, Sebasoni; Kamande, Mercylin (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2021)
Civility practices in the workplace are very crucial if the organization wants to increase its marketing outcomes mainly in financial institutions. In this regard, the researcher sought to conduct research in regard to the impact of civility practices in the workplace on the marketing outcomes with a case of I & M Bank Ltd in Nyarugenge District. Three specific objectives have guided this study; namely to assess the nature of civility practices in the marketing department of I & M Bank Rwanda Ltd, to evaluate the performance of the marketing team in I & M Bank Rwanda Ltd in relation to civility; and assess the relationship between civility practices at workplace and marketing outcomes at I & M Bank Rwanda Ltd. The research was guided by confusion theory, marketing theory and neoclassical theory. The target population of this study is 126 employees. This study used descriptive research design with 126 respondents through use of census as the method of sampling. The interview guide, questionnaire and observational method were used during data collection. To test the validity and reliability of research tools, a pilot study of 14 respondents was done before actual period of data collection and it proved validity of 0.86 which is above 0.7 of content validity index; data analysis was done with the help of SPSS Version 21 while coding, editing and cleaning the data collected from the field by use of primary and secondary data sources. The results have demonstrated a remarkable positive and significant relationship between working relationship and moral interaction (r=0.899 and sig=0.00), between working relationship and mutual respect (r=0.943 and sig=0.00), between moral interaction and mutual respect (r=0.907 and sig=0.00), between customer retention and sales revenue (r=0.927 and sig=0.00), between customer retention and market share (r=0.901 and sig=0.00), between sales revenue and market share (r=0.914 and sig=0.00), between customer relation and working relationships (r=0.888 and sig=0.00), between sales revenue and working relations (r=0.911 and sig=0.00), between market share and working relationship (p=0.891 and sig=0.00), between moral interaction and market share (r=0.853 and sig=0.00) because all calculated p-values have a degree of significance which less than 0.01. Therefore, it implies that significant and positive relationship occurred between civility practices and the marketing outcomes in I & M Bank Rwanda Ltd. Based on the above findings, the researcher encouraged I & M Bank employees to always handle customers with kindness, courteous, respect and civil behavior to ensure the coexistence of civility and marketing outcomes that can only be enhanced by customer care provided to clients of I&M Bank Rwanda Ltd